1988
DOI: 10.2331/suisan.54.283
|View full text |Cite
|
Sign up to set email alerts
|

Post-mortem degradation of inosinic acid and related enzyme activity in the dark muscle of fish.

Abstract: In order to elucidate the degradation of inosinic acid (IMP) in the dark muscle of fish, the levels of adenine nucleotides and their related compounds were compared in the white and dark muscles of yellowtail Seriola quinqueradiata and in common mackerel Scomber japonicas during iced storage.The struggling of 30 minutes before death affected the degradation rate of IMP in the dark muscle of yellowtail, while it did not affect in the white muscle. During iced storage, the degradation of IMP proceeded very rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…It was already reported that the IMP degrading activity in dark muscle was higher than that in ordinary muscle. 14,15 From these findings, it was considered that the IMP degrading activity might be higher in the order of red, pink, and white muscle, and the interposition of pink muscle fiber into dorsal ordinary muscle might considerably accelerate the post‐mortem temporal change of K‐value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was already reported that the IMP degrading activity in dark muscle was higher than that in ordinary muscle. 14,15 From these findings, it was considered that the IMP degrading activity might be higher in the order of red, pink, and white muscle, and the interposition of pink muscle fiber into dorsal ordinary muscle might considerably accelerate the post‐mortem temporal change of K‐value.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Furthermore, it is known that IMP degrading activity in dark muscle is higher than that in ordinary muscle. 14,15 These findings suggest that IMP degrading activity varies among muscle fiber types of red, pink, and white muscle fibers and then the temporal change of K‐value may also be different.…”
Section: Introductionmentioning
confidence: 87%
“…Recently, in serial studies on muscle fiber types of the dorsal ordinary muscle in fish, Jabarsyah et al 13 have reported that the dorsal ordinary muscle in many fish species is composed of not only white muscle fibers, but also pink muscle fibers arranged in a mosaic pattern. And it is also known that the IMP degrading activity in dark muscle is higher than that in ordinary muscle 14,15 . These findings suggest that the IMP degrading activity may be different among red, pink, and white muscle fibers and also that the interposition of pink muscle fibers into the dorsal ordinary muscle may influence the temporal change of K‐value.…”
Section: Introductionmentioning
confidence: 85%
“…It was reported that the post-mortem changes in scallop adductor were closely related to the eating quality of the flesh (Massa et al, 2003). As the rate and pattern of post-mortem changes in nucleotides and their related compounds differ considerably for fish species (Ryder, 1985), muscle types (Obatake et al, 1988), and factors related to handling and storage conditions (Surette et al, 1988), ATP degradation can be used as a good reference. Besides, the chemical assessment of the freshness in post-mortem storage has not yet been well established for bivalves (Suwetja et al, 1989;Yokoyama et al, 1992).…”
Section: Introductionmentioning
confidence: 98%